HUBUNGAN MEKANISME KOPING DENGAN PENURUNAN STRESS ODHA - Fabanyo, Rizqi Alvian; Setia Anggreini, Yogik (Nursing Arts, 2023)
ABSTRACTHIV/AIDS is one of the important global health problems because of the high frequency and mortality rate, by using adaptive coping mechanisms it is expected to influence individuals in solving problems, overcoming changes that occur and threatening situations both cognitively and behaviorally. This study aims to determine coping mechanisms reslationship with stress reduction of ODHA at Yayasan Sorong Sehati Sorong City. Methods of this study uses a quantitative research that is analytic correlation with a cross sectional research design. The sample used was 30 respondents. The research instrument used was a coping mechanisms questionnaire and a stress questionnaire. The results of statistical tests using the chi square test obtained the value of p-value = 0.443 a =0.05. So that there is no relationship between coping mechanisms and stress reduction.Keywords: Coping mechanism; stress reduction; ODHA